Male Homosexuality and Lesbianism in the Academic Production of Psychology: A Systematic Bibliographic Review Between 2012-2016 - Yang, Jinfang; Íñiguez-Rueda, Lupicinio (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
The aim of the article is to identify the academic productions on male homosexuality and the lesbianism of Psychology as a discipline of Latin America, Spain and Portugal during 2012-2016. The review was carried out in the databases: VHL, Dialnet, PsycINFO, Redalyc, Scopus and Web of Science. We identified 80 articles from Spain, 63 from Portugal and 289 from Latin America, considering the cooperative works altogether there are 420 identified articles. We classify the topics into 12 categories in order to organize the research approaches: attitude; health; family and love relationships and friendship; gender and identity; equality, rights, social support and education. By continuing investigating male homosexuality and lesbianism without questioning heterosexuality, psychology has figured the sexual (a)normality of the society considering that the scientific knowledge has effects on everyday life.